Adolescent Alcohol and Stress Exposure Rewires Key Cortical Neurocircuitry - Sicher, Avery R.; Duerr, Arielle; Starnes, William D.; Crowley, Nicole A. (Frontiers in Neuroscience, 2022)
Human adolescence is a period of development characterized by wide ranging emotions and behavioral risk taking, including binge drinking (Konrad et al., 2013). These behavioral manifestations of adolescence are complemented by growth in the neuroarchitecture of the brain, including synaptic pruning (Spear, 2013) and increases in overall white matter volume (Perrin et al., 2008). During this period of profound physiological maturation, the adolescent brain has a unique vulnerability to negative perturbations. Alcohol consumption and stress exposure, both of which are heightened during adolescence, can individually and synergistically alter these neurodevelopmental trajectories in positive and negative ways (conferring both resiliency and susceptibility) and influence already changing neurotransmitter systems and circuits. Importantly, the literature is rapidly changing and evolving in our understanding of basal sex differences in the brain, as well as the interaction between biological sex and life experiences. The animal literature provides the distinctive opportunity to explore sex-specific stress- and alcohol- induced changes in neurocircuits on a relatively rapid time scale. In addition, animal models allow for the investigation of individual neurons and signaling molecules otherwise inaccessible in the human brain. Here, we review the human and rodent literature with a focus on cortical development, neurotransmitters, peptides, and steroids, to characterize the field’s current understanding of the interaction between adolescence, biological sex, and exposure to stress and alcohol.